Evaluation of temperature on the biological activities and fertility potential during vermicomposting of pig manure employing Eisenia fetida. (15th June 2021) - Zhou, Yong; Zhang, Dan; Zhang, Yunfeng; Ke, Jingshi; Chen, Deli; Cai, Minggang
Abstract: In this laboratory-scale study, the biological activities and vermicomposting potential of Eisenia fetida in pig manure were investigated to evaluate the influence of temperature (10°C–50 °C) on vermicomposting effect. The enzyme activities of catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), and the content of malondialdehyde (MDA) in earthworm, macro-nutrients (N, P, K), total organic carbon (TOC), humification index (HIX) and C/N ratio in pig manure have been investigated simultaneously. Results revealed that CAT activity elevated initially and then declined with the increased temperature. The increased POD, SOD activity and MDA content indicated the antioxidant stress response of earthworm and the optimum temperature was found at 30 °C. After vermicomposting the pig manure for 60 d under temperature range of 10°C–50 °C, the vermicompost exhibited a significant increase in macro-nutrients, whereas a reduction was observed in TOC, C/N ratio and HIX, reflecting the efficient decomposition of organic waste driven by earthworms and microorganisms synergistically. The result of total microbial population showed the increase of actinomycetes and bacterial population. The enhancement percentage was in the order: 30 °C > 40 °C > 50 °C > 20 °C > 10 °C, revealing the impact of temperature. The results indicated the advantage of vermicomposting with Eisenia fetida and the regulation mechanism of temperature on the vermicomposting effect of pig manure. The present study will benefit to the utilization of agricultural wastes and achieving environmental sustainability. Highlights: Vermicomposting is a method for transforming pig manure into an organic fertilizer. The 50 °C can promote the natural composting, but would inhibit the vermicomposting. The gut bacterial population can enhance the vermicomposting process at the 30 °C. The composting process can find out the mechanism of temperature regulation.